Hubungan Suku Bunga dan Inflasi: Studi Empiris di Indonesia - Suseno, Adinda Maharani; Agusalim, Lestari (Journal of Economic, Management and Entrepreneurship, 2024)
This study aims to analyze the effectiveness of the monetary policy transmission mechanism through the interest rate channel on inflation in Indonesia. The economic variables used in this study include the Bank Indonesia interest rate, deposit interest rate, and loan interest rate, with data spanning from January 2011 to December 2023. The method employed is the Error Correction Model (ECM) analysis, which allows the researcher to evaluate the relationship between these variables in both the short and long term. The results of the ECM analysis show that the Bank Indonesia interest rate, as one of the primary instruments of monetary policy, has a positive and statistically significant relationship with inflation in both the short and long term. In other words, each increase in the Bank Indonesia interest rate consistently raises inflation during both periods, highlighting the key role of the benchmark interest rate in the transmission of monetary policy in Indonesia. On the other hand, the variables of the deposit interest rate and loan interest rate exhibit different results. Both variables show a negative and statistically significant relationship with inflation in the short and long term. This means that an increase in the deposit and loan interest rates tends to reduce inflation, indicating that raising interest rates in these instruments can help mitigate inflationary pressures by curbing consumption, investment, and the amount of money circulating in the market. This study provides important insights into how the monetary policy transmission mechanism operates in Indonesia through the interest rate channel and highlights the differing impacts of the Bank Indonesia interest rate and other interest rates on inflation over various timeframes.